Wind power development and its status in Sri Lanka - Atputharajah, A.; Tennakoon, A.P.; Chandrasena, R.P.S.; Ekanayake, J.B.; Abeyratna, S.G. (My University, 2007)
Wind power has become the most significant option among renewable energy based electricity generation due to its wider availability and zero environmental pollution. Advancement in technologies, especially wind turbine configurations, their control features and high power electronics has increased the single turbine rating to over 5 MW and the total installed capacity to 74GW in the world. Among the renewable energy sources available in Sri Lanka, wind power has been identified as the most promising renewable power option for large power generation. The Pre-Electrification Unit of Ceylon Electricity Board has carried out a wind resource assessment study in Puttalam and Central Regions of the country in 2002. The wind energy resource atlas of Sri Lanka and Maldives was developed by the National Renewable Energy Laboratory in 2003. It also has revealed that there are many areas that are estimated to have “Good” to “Excellent” wind resources in Sri Lanka. These studies have revealed that the overall wind potential in the open land area is 8 MW/km2. However, wind power development in Sri Lanka is not at a satisfactory level and it has some technical, logistical as well as policy constraints. At present, only 3 MW gridconnected pilot wind power plant is available in the country at Hambantota. It has been commissioned in 1999 and the monthly plant factor has been in the range of 5% to 15% in year 2006. This is relatively low plant factor. This paper discusses the wind power development in the world and summarizes the status in Sri Lanka. Possible research areas, that need to be motivated in Sri Lanka to check the feasibility of wind power generation, are also discussed.